Distance music learning: Methodological and technological aspects - Pereira, Fabiano Lemos (Revista Hipótese, 2022)
Through a bibliographic review, this work presents a selection of technological and methodological aspects that distance music education has permeated. As main authors, Keith Swanwick (2003, 2014) and Daniel Gohn (2011) stand out. In the end, it is concluded that the current technological aspects cannot integrate the generics tools of Learning Management System (LMS) with the various existing musical resources and, in addition, the management of Distance Education courses (DE) does not have take into account the specificities of Music courses, in addition to the need for technological mastery on the part of the teacher and the student.
Keywords: Musical education; Music technology; Distance education; Distance music education; Methodology and technology in music education